1999
DOI: 10.1111/j.1348-0421.1999.tb03355.x
|View full text |Cite
|
Sign up to set email alerts
|

A Clostridium perfringens hem Gene Cluster Contains a cysGB Homologue That Is Involved in Cobalamin Biosynthesis

Abstract: The hem gene cluster, which consists of hemA, cysGB , hemC, hemD, hemB, and hemL genes, and encodes enzymes involved in the biosynthetic pathway from glutamyl-tRNA to uroporphyrinogen III, has been identified by the cloning and sequencing of two overlapping DNA fragments from Clostridium perfringens NCTC8237. The deduced amino acid sequence of the N-terminal region of C. perfringens HemD is homologous to those reported for the C-terminal region of Salmonella typhimurium CysG and Clostridium josui HemD. C. perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…S1). Moreover, the candidate genes were selected based on previous studies that have shown that the deletion of these genes affect cobalamin biosynthesis in other bacterial species [ 47 , 50 , 51 ]. We also evaluated the transcriptional response of eutV, a transcriptional regulator of the ethanolamine operon.…”
Section: Methodsmentioning
confidence: 99%
“…S1). Moreover, the candidate genes were selected based on previous studies that have shown that the deletion of these genes affect cobalamin biosynthesis in other bacterial species [ 47 , 50 , 51 ]. We also evaluated the transcriptional response of eutV, a transcriptional regulator of the ethanolamine operon.…”
Section: Methodsmentioning
confidence: 99%